Synthesis and characterisation of carbon nanotubes from hydrocarbon-rich flames - Tan, Win Hon (2017)
The present study focuses on the synthesis and characterisation of carbon nanotubes (CNTs) synthesised from flame at atmospheric condition. A laminar flame burner was utilised to establish a rich premixed propane/air flame. The flame was impinged on a stainless steel wire mesh coated with nickel (Ni) catalyst to grow CNTs. Parametric studies were conducted to investigate the optimum operating conditions for CNTs yields. The effects of equivalence ratios, substrate mesh number and the distance between the burner nozzle outlet and substrate on the yield of CNTs were investigated. The CNTs formed on the substrate were collected and characterised by using scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX), X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA). CNTs were grown on the substrate impinged by the main reaction zone of the flame. The FESEM micrograph showed that CNTs produced were in disarray. Parametric studies showed that substrate with mesh number 80 at the distance of 10 cm from burner outlet, total air/propane flow rate of 1.2 g/s, mixture of fuel/air at ? 2.2 produced optimum yield of CNTs during 15 minutes of flame synthesis process. Analysis of the TEM micrographs shows the average diameter of CNTs are 11.3 -12.3 nm and interplanar spacing (002), d002 is approximately 0.31 nm. XRD results showed the characteristic CNTs (002) peak is found at 2? ~26°. Distinctive G-band and D-band for CNTs were observed from Raman spectra for samples produced. TGA analysis showed that 75 % of CNTs present in the sample has oxidation temperature of 510 °C. The purity and quality of the CNTs were improved by using H2O2 and HCl treatments, whereby CNTs with purity of 92.9 % and thermal stability of 556 °C were obtained.